Modifications of pyruvate handling in health and disease - Sugden, Mary (Henry Stewart Talks, 2007)
Potential metabolic fates of pyruvate, Lactate transport, Role of pyruvate dehydrogenase complex (PDC), Regulation of PDC, Mechanisms of activation of PDC by pyruvate dehydrogenase phosphatases, Pyruvate dehydrogenase kinase (PDK) expression and regulation, Multi-site phosphorylation, Transcription factors regulating PDK4 expression, Anaplerosis and cataplerosis, Pyruvate carboxylase, Insulin secretion and action, Glucose/fatty-acid cycle, Consequences of PDK4 upregulation, Disorders of pyruvate handling